Spontaneous Coronary Dissection in Late Puerperium: Now What? A Case Report - Vicente, Miguel; Zenzela, Dinis; Ramos, Domingos; Gonçalves, Lino (Brazilian Journal of Case Reports, 2024)
Spontaneous coronary dissection is an infrequent cause of non-atherosclerotic or iatrogenic acute coronary syndrome, predominantly diagnosed in women under 50 years old during their reproductive phase, usually without associated cardiovascular risk factors. Various factors underlie its occurrence, ranging from connective tissue diseases to intense emotional stress, with fibromuscular dysplasia being a commonly associated nosological entity. Coronary angiography is the preferred diagnostic examination, and a conservative strategy is frequently recommended, especially in stable contexts. Invasive strategies, such as surgical revascularization or percutaneous coronary intervention, are reserved for more complex clinical situations involving severe arrhythmias or dissections involving the left coronary artery trunk, among others. We present the case of a postpartum woman with no known cardiovascular risk factors, diagnosed with spontaneous coronary dissection in the late puerperium of a twin pregnancy, resulting in a fatal outcome.